Analisis Yuridis Tanggung Jawab dan Ganti Rugi Akibat Wanprestasi dalam Perjanjian Jual Beli Berdasarkan KUHPerdata: A Juridical Analysis of Liability and Compensation for Breach of Contract in Sales Agreements Under the Indonesian Civil Code - Ryan Andrea; Dian Herlambang; Dina Haryati Sukardi (LAWYER: Jurnal Hukum, 2026)
A sale and purchase agreement is a form of obligation that provides legal certainty for the parties involved. However, instances of default (breach of contract) frequently occur during implementation, resulting in losses and raising issues regarding legal liability and the awarding of compensation. This study aims to analyze legal liability arising from default in sale and purchase agreements under the Indonesian Civil Code (*Kitab Undang-Undang Hukum Perdata* or KUHPerdata), as well as the mechanisms for awarding compensation to the aggrieved party. The study employs a normative-juridical method utilizing statutory and conceptual approaches. Research data consists of secondary data obtained through literature review and analyzed qualitatively. The findings indicate that legal liability arises when there is a valid agreement, a default, a loss, and a causal link between the default and the loss. Forms of liability include performance of the obligation, payment of compensation, rescission of the agreement, or other legal consequences as stipulated in the Civil Code. The awarding of compensation is governed by Articles 1243–1248 of the Civil Code, covering costs, losses, and interest. Consistent application of these provisions—based on the principles of legal certainty, justice, and good faith—is expected to provide effective legal protection for the parties involved.